2023
DOI: 10.1161/strokeaha.122.042290
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Macrophages Mediate Microvasospasms After Experimental Subarachnoid Hemorrhage

Abstract: BACKGROUND: Subarachnoid hemorrhage (SAH) is characterized by acute and delayed reductions of cerebral blood flow (CBF) caused, among others, by spasms of cerebral arteries and arterioles. Recently, the inactivation of perivascular macrophages (PVM) has been demonstrated to improve neurological outcomes after experimental SAH, but the underlying mechanisms of protection remain unclear. The aim of our exploratory study was, therefore, to investigate the role of PVM in the formation of acute microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another postulated mechanism involves anti-inflammatory properties of milrinone through inhibition of cytokines production 35 , since inflammation is also suspected to play a role in DCI development 53 . For instance, perivascular macrophage have been shown to participate in microvascular spasms in experimental models, and could therefore be a cellular target for milrinone non-vascular effects 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Another postulated mechanism involves anti-inflammatory properties of milrinone through inhibition of cytokines production 35 , since inflammation is also suspected to play a role in DCI development 53 . For instance, perivascular macrophage have been shown to participate in microvascular spasms in experimental models, and could therefore be a cellular target for milrinone non-vascular effects 54 .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we used clodronate liposomes (CLO) as a reagent to deplete PVM. Depletion of PVM by CLO injection into the CSF via the cisterna magna is a well-established method (Drieu et al, 2022;Lin et al, 2023); CLO are phagocytosed by macrophages and induce their apoptotic cell death (Van Rooijen et al, 1996). Compared to control liposomes (encapsulated PBS), CLO injection induced depletion of PVM in the lumbar spinal cord at 3 and 7 days after injection, but the number of PVM was restored at 14 days after injection (Figures 3A, B).…”
Section: Repetitive Intracisternal Injection Of Clodronate Liposomes ...mentioning
confidence: 96%
“…In this disease context, the interaction of endothelial cells and PvMΦ impaired the BBB and resulted in vascular dysfunction, leading to cognitive deficits in chronic hypertension [ 31 ]. Other studies in experimental subarachnoid haemorrhage showed that intracerebroventricular injected clodronate liposomes depleted PvMΦ and delayed blood clearance but had a beneficial effect on neuronal cell death, neuroinflammation, neurological impairment, and microvasospasms [ 68 , 123 ]. These studies show that PvMΦ effects on BBB function are variable, which may be related to either the experimental set-ups/model investigated or potentially the heterogeneity of PvMΦ in different locations, at different developmental stages or under different metabolic conditions.…”
Section: Microglia and Perivascular Macrophages (Pvmφ) Control Bbb Pe...mentioning
confidence: 99%